De-novo genome assembly and annotation of sobaity seabream Sparidentex hasta - Karam, Qusaie; Kumar, Vinod; Shajan, Anisha B.; Al-Nuaimi, Sabeeka; Sattari, Zainab; El-Dakour, Saleem (Frontiers in Genetics, 2022)
Sparidentexhasta (Valenciennes, 1830) of the Sparidae family, is an economically important fish species. However, the genomic studies on S. hasta are limited due to the absence of its complete genome. The goal of the current study was to sequence, assemble, and annotate the genome of S. hasta that will fuel further research related to this seabream. The assembled draft genome of S. hasta was 686 Mb with an N50 of 80 Kb. The draft genome contained approximately 22% repeats, and 41,201 genes coding for 44,555 transcripts. Furthermore, the assessment of the assembly completeness was estimated based on the detection of ∼93% BUSCOs at the protein level and alignment of >99% of the filtered reads to the assembled genome. Around 68% of the predicted proteins (n = 30,545) had significant BLAST matches, and 30,473 and 13,244 sequences were mapped to Gene Ontology annotations and different enzyme classes, respectively. The comparative genomics analysis indicated S. hasta to be closely related to Acanthopagrus latus. The current assembly provides a solid foundation for future population and conservation studies of S. hasta as well as for investigations of environmental adaptation in Sparidae family of fishes. Value of the Data: This draft genome of S. hasta would be very applicable for molecular characterization, gene expression studies, and to address various problems associated with pathogen-associated immune response, climate adaptability, and comparative genomics. The accessibility of the draft genome sequence would be useful in understanding the pathways and functions at the molecular level, which may further help in improving the economic value and their conservation.